İBNU'T-TARÂVE'NİN ARAP DİLİNDEKİ YERİ - DAĞ, ZEYNEP (Fırat Üniveristesi, 2016)
İbnu't-Tarâve, hicri 5. asrın sonlarına doğru Endülüs'te yetişmiş büyük nahiv âlimlerinden birisidir. Endülüs'te ilmi faaliyetlerin yoğun olduğu bir dönemde yaşamış ve dönemin meşhur âlimlerinden nahvin yanı sıra fıkıh ve hadis alanında da eğitim almıştır. Eğitimini tamamladıktan sonra Meriye'ye yerleşmiş ve uzunca bir süre burada nahiv dersleri okutmuştur. Burada okuttuğu dersler ile haklı bir şöhret kazanan İbnu't-Tarâve, yaşadığı dönemde nahiv ve edebiyatta kemâl derecesine ulaşanlara verilen üstat lakabıyla anılmaya başlamıştır. Büyük dil âlimi Sibeveyhî'ye ve onun eseri olan el-Kitâb'a olan bağlılığı ile tanınan İbnu't-Tarâve, zaman zaman Sibeveyhî'nin görüşlerine aykırı görüşler ortaya koymuştur. Ayrıca birçok konuda, büyük dil otoriteleri kabul edilen Ebû Ali el-Fârisi ve Zeccâcî'nin görüşlerini de tenkit etmiştir. Bu eleştirileri sebebiyle Arap dili ve edebiyatı tarihinde daha çok muhalif tavrıyla bilinen bir âlimdir. Nahiv alanında özgün görüşleri de bulunan İbnu't-Tarâve, bazı konularda Basra ekolünün bazı konularda ise Kûfe ekolünün görüşlerini benimsemiştir. Tezimizde İbnu't-Tarâve'nin bu görüşlerini tespit ve tahlil etmeye çalışacağız. Anahtar Kelimeler: İbnu't-Tarâve, Endülüs, Nahiv Usulü, Basra Ekolü, Kûfe Ekolü, Risaletu'l-İfsah

Ibn al-Tarawah is one of the great Arabic syntax scholars who had grown up in Andalusia towards to the end of the 5th century. He had lived in a period when the scientific activities in Andalusia were very intense and he had been educated by famous scholars of this period in fiqh and hadith as well as Arabic syntax. He had settled in Almeria after completing his education and he had taught Arabic syntax lessons here for a long time. Ibn al-Tarawah who had earned a rightful reputation with the lessons he had taught here had started to be mentioned as ustaat / master teacher which was given to ones who reached maturity level in Arabic syntax and literature in the period that he lived. Ibn al-Tarawah who is known as dependent on the great language scholar Sibawayh and his book al-Kitab had occasionally revealed views contrary to Sibawayh's views. Furthermore, he had criticized in many topics, views of Abu Ali al-Farisi and az-Zaccaci who have been known as big language authorities. Because of those criticisms he has been known for his contrarian attitude in the history of the Arabic language and rhetoric. Ibn al-Tarawah who had specific original views in Arabic syntax had adopted views of Basrah school in some matters as well as Kufa school in some matters. We will try to identify and analyze those views of Ibn al-Tarawah in our thesis. Key Words: Ibn al-Tarawah, Andalusia, Arabic Syntax Method, Basrah School,Kufa School, Rsalah alifsah
The place of İbn al-Tarawah in the Arabic language
Keywords: Doğu Dilleri ve Edebiyatı